Influence of paleo-uplift on structural deformation of salt-bearing fold-and-thrust belt: Insights from physical modeling. (December 2021) - Long, Yi; Chen, Hanlin; Cheng, Xiaogan; Deng, Hongdan; Lin, Xiubin
Abstract: Paleo-uplift is one of the main controlling factors that influence the style of deformation in salt-bearing fold-and-thrust belt (FTB). Whereas, how paleo-uplift amplitude influences salt-related deformations in FTB remains unclear. Here we designed four series of experimental models that contain a basal brittle décollement and a shallow ductile décollement . Our studies show that the presence of paleo-uplift in the ductile décollement has a profound impact on deformation propagation in the supra-salt overburden during the contraction, which localizes shortening strain in the proximal and central parts of the models and deters rapid deformation propagation towards the distal part. As the amplitude of the paleo-uplift increases, its influence on deformation propagation becomes stronger, resulting in out-of-sequence deformation towards the hinterland. The increase of paleo-uplift amplitude also controls the distribution and migration of rock salt during the contraction. Particularly, when the paleo-uplift height equals or exceeds the thickness of salt layer, the position of salt pinch-out or welding point localizes shortening strain and thereby initiates folding and thrusting deformation over the salt-base high. This process leads to salt fed into the fold and fault belt over the paleo-high and the uplift of the supra-salt layers. Our modeling results are highly comparable with natural examples of Kuqa FTB and provide insights to the salt-influenced deformations in the Qiulitage structural belt. Highlights: The presence of paleo-uplift has a profound impact on deformation propagation in the supra-salt overburden. The increase of paleo-uplift amplitude controls the distribution and migration of rock salt during the contraction. Higher amplitude paleo-uplift results in localized deformation and salt thickening.